Prevalence of Stylohyoid Ligament Calcification on Panoramic Radiographs in an Iranian Population - Zahra Shakibaei; Elahe Tohidi; Fatemeh Salemi; Samira Saati (Mashhad University of Medical Sciences, 2014)
Introduction: The aim of this study was to investigate the prevalence of stylohyoid ligament complex elongation in a group of Iranian patients using digital panoramic radiographs. Methods: Panoramic radiographs of 1211 patients (684 females and 527 males) referred to the dental school of Hamadan university of medical science were selected from 2011 to 2013. The stylohyoid ligament complexes were investigated. Results: This abnormality was seen in both sexes. A calcified complex was found in 632 (52.2 %) of the patients. Both-sided (right and left) type 1 calcified complex (according to O'Carroll classification) was observed in 207 patients, while types 2-4 were found in 204, 112, and 109 patients, respectively. Conclusion: The results suggest that stylohyoid ligament calcification complex is frequent in Iranian population and present in both sexes with equal distribution. In addition, calcifications were seen more often at age of 20-40 years, and the extent of calcification did not show a tendency to increase with age.